Different Expression Levels of Human Mutant Ubiquitin B+1 (UBB+1) Can Modify Chronological Lifespan or Stress Resistance of Saccharomyces cerevisiae - Muñoz-Arellano, Ana Joyce; Chen, Xin; Molt, Andrea; Meza, Eugenio; Petranovic, Dina (Frontiers in Molecular Neuroscience, 2018)
The ubiquitin-proteasome system (UPS) is the main pathway responsible for the degradation of misfolded proteins, and its dysregulation has been implicated in several neurodegenerative diseases, including Alzheimer’s disease (AD). UBB+1, a mutant variant of ubiquitin B, was found to accumulate in neurons of AD patients and it has been linked to UPS dysfunction and neuronal death. Using the yeast Saccharomyces cerevisiae as a model system we constitutively expressed UBB+1 to evaluate its effects on proteasome function and cell death, particularly under conditions of chronological aging. We showed that the expression of UBB+1 caused inhibition of the three proteasomal proteolytic activities (caspase-like (β1), trypsin-like (β2) and chymotrypsin-like (β5) activities ) in yeast. Interestingly, this inhibition did not alter cell viability of growing cells. Moreover, we showed that cells expressing UBB+1 at lower level displayed an increased capacity to degrade induced misfolded proteins. When we evaluated cells during chronological aging, UBB+1 expression at lower level, prevented cells to accumulate reactive oxygen species (ROS) and avert apoptosis, dramatically increasing yeast life span. Since proteasome inhibition by UBB+1 has previously been shown to induce chaperone expression and thus protect against stress, we evaluated our UBB+1 model under heat shock and oxidative stress. Higher expression of UBB+1 caused thermotolerance in yeast due to induction of chaperones, which occurred to a lesser extent at lower expression level of UBB+1 (where we observed the phenotype of extended life span). Altering UPS capacity by differential expression of UBB+1 protects cells against several stresses during chronological aging. This system can be valuable to study the effects of UBB+1 on misfolded proteins involved in neurodegeneration and aging.